2016
DOI: 10.4018/jitr.2016100103
|View full text |Cite
|
Sign up to set email alerts
|

Critical Factors Influencing E-Government Adoption in India

Abstract: In this paper, the authors present an integrated model based on Unified Theory of Acceptance and Use of Technology (UTAUT), trust and citizen satisfaction, to explore the factors which influence the adoption of e-government services in Delhi (India). The findings indicate that effort expectancy, performance expectancy, and trust in technology followed by trust in government, citizen satisfaction, and facilitating conditions are significant predictors of citizen adoption of e-government. The findings also revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…The largest number of studies proposed their future research directions in terms of the need for diverse sample (e.g. [22], [30]), which are aligned with the limitations of existing research as presented earlier where the highest 14 studies articulated that their sample was context specific. This is followed by some other future research directions including the need for the proposed model to be tested using longitudinal data (e.g.…”
Section: Limitations and Recommended Future Research Of Reviewed Studiesmentioning
confidence: 85%
See 3 more Smart Citations
“…The largest number of studies proposed their future research directions in terms of the need for diverse sample (e.g. [22], [30]), which are aligned with the limitations of existing research as presented earlier where the highest 14 studies articulated that their sample was context specific. This is followed by some other future research directions including the need for the proposed model to be tested using longitudinal data (e.g.…”
Section: Limitations and Recommended Future Research Of Reviewed Studiesmentioning
confidence: 85%
“…The findings indicated that the unified theory of acceptance and use of technology (UTAUT) (10) (e.g. [7], [30]) has been used the most number of times closely followed by the technology acceptance model (TAM) (9) (e.g. [8]).…”
Section: Theories/models Usedmentioning
confidence: 99%
See 2 more Smart Citations
“…A lot of researchers and scientists have been working in the field of IT audit and analyzing various features and different attributes, and issues of cybersecurity [6]. E-government issues themselves were also analyzed by researchers, emphasizing such aspects as e-government inerrability, adoption, quality [7], efficiency [8], and others. Before assessing IT audit in the public sector, and analysing specifics, we are to discuss in short classification and development stages.…”
mentioning
confidence: 99%